IMPACT OF GLOBALISATION ON MARGINALISED GROUPS IN INDIA - Gudigonda, Yuvaraju (IJRDO - Journal of Social Science and Humanities Research, 2022)
After globalisation and urbanisation brought about many changes in Indian culture, Indian society is radically altering. Economic policies directly influence how the economy’s structural foundation is shaped. Government-formulated and -implemented economic policies have also been crucial in determining the levels of income, savings, investments, and employment in society. Assuming that India can evaluate an effective machinism for economic reforms would be a mistake, and it would be difficult for India to adopt global changes without addressing domestic issues like the fight against terrorism, employment for educated rural residents as well as the rural poor, emancipation of women and marginalised groups, and fair prices and market facilities for farmers, among others, would be difficult. As a result of the numerous new areas of conflict and cooperation brought about by globalisation, India’s economy can now be more fully integrated into the global economy on the premise of safeguarding our own national interests. In order to comprehend rising inequality in India, this essay examines how globalisation affects concerns of social justice and well-being and demonstrates how it has an impact on the disadvantaged.